Clinical profile and outcome of Hantavirus infection with renal involvement in India - Kumar, Alok; Khrime, Dorchhom; Bansal, Nitin; Pandey, Amar Nath; Ahmad, Shakeel; Amit, Varma (International Journal of Research in Medical Sciences, 2017)
Background:Hantavirus infections are found all over world but there is paucity of information about clinical features of Hantavirus infection in India.Aim of current study was to study clinical profile and outcome of patients with Hantavirus infection and renal insufficiency who presented at our institute. Methods:All patients who were admitted in department of medicine with Hantavirus infection and renal insufficiency were included. Their basic demographic profile with relevant laboratory investigations was recorded. They were diagnosed with Hantavirus infection if they had positive IgM antibodies by ELISA test. Results:There were seven patients with mean age of 54 years. They had mean serum creatinine level of 4.37 ± 1.86 mg%. All had thrombocytopenia and hepatic dysfunction as well. Five patients had hypotension. There was need of dialysis in three patients. They also had hypoalbuminemia. No patient had features suggestive of acute respiratory distress syndrome. All patients had recovery of renal function and there was no mortality. Conclusion:Patients with Hantavirus infection presented like hemorrhagic fever with renal syndrome. Their outcome is good. We need to suspect Hantavirus infection in appropriate clinical scenario in India.